EFFECT OF SALINITY AND SIZE ON THE ABSORPTION (Uptake)CONTAMINANTS OF METAL Zn IN BLOOD COCKLE - Fadel Fadel; Yusni Ikhwan Siregar; Irvina Nurrachmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTBlood cockle interact with physical and chemical oceanography factors caused by the tide intensely, so it’s not posible to blood coockle to free from heavy metal pollution. As a organisms, blood cockle are relatively sedentary and filter feeder, so that the presence of pollutants in the marine waters will be absorbed by the biota. Research on the absorption of zinc (Zn) with different salinity level and shell size was conducted in December 2017, it aims to determine the ability of zinc (Zn) absorption in blood cockle based on salinity level and shell size differences. The method used is experimental method using Factorial Randomized Block Design which is designed from 2 factors namely salinity and shell size. The absorption of Zn by blood cockles were higher at 20‰ compared to 25‰ as well as the uptake by 3 cm shells length of the cockles were higher than that by the cockles with 4,5 cm length. Based on the results of this study it can be concluded that the absorption of Zn in blood cockles in influenced by the difference of salinity and shell sizes.Key Words: Blood cockles, Salinity, Size.